Bank Lending Margins in the Euro Area: The Effects of Financial Fragmentation and ECB Policies - Helen Louri; Petros M. Migiakis (London School of Economics and Political Science (LSE), European Institute, 2016)
In the present paper we study the determinants of the margins paid by euro-area non-financial corporations (NFCs) for their bank loans on top of the rates they earn for their deposits (bank lending margins). We use panel VAR techniques, in order to test for causality relationships and produce impulse response functions for eleven euro-area countries from 2003:1 to 2014:12. The countries are separated into two groups (distressed and non-distressed), in order to examine for heterogeneities in the relationships between lending margins; the period is also separated with reference to the peak of the global financial crisis (before and after the collapse of Lehman in September 2008). We find that significant heterogeneities existed even before the global financial crisis and remained in its aftermath, although the magnitude and the direction of the effects exercised by the explanatory variables have changed. Furthermore, apart from finding that market concentration and the prudence of banks' management increase the lending margins NFCs pay for their loans, there is evidence of substitution effects between financing obtained from banks and corporate bond markets. The provision of ample liquidity from the ECB, in the aftermath of the global financial crisis was found to be effective only for the core countries, suggesting that further policy actions are needed in order to reduce the fragmentation of bank lending and promote financial integration to the benefit of the euro-area real economy.
Keywords: E44; E51; E58; F36; F42; 330; bank lending margins; financial fragmentation; global financial crisis; ECB; euro area